2009
DOI: 10.1093/heapol/czp029
|View full text |Cite
|
Sign up to set email alerts
|

Formal and informal payments in health care facilities in two Russian cities, Tyumen and Lipetsk

Abstract: Informal payments for health care services are common in many transition countries, including Russia. While the Russian government proclaims its policy goal of improving access to and quality of free-of-charge health services, it has approved regulations that give local authorities the right to provide services against payment. This paper reports the results of a population-based survey (n = 2001) examining the prevalence of the use of medical services for which people pay formally or informally in two regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 13 publications
3
60
0
Order By: Relevance
“…We have explored the phenomenon in the context of Iran's health system by involving three main stakeholders. Previous studies have reported that people make informal payments to express gratitude (3,24,25), to get additional or better services (3,26), or because of cultural norms ingrained in their tradition, and weak laws (25). This study indicates that all of the above mentioned factors affect patients' decisions to make such payments, although some of them seem to play a more important role.…”
Section: Discussionmentioning
confidence: 62%
“…We have explored the phenomenon in the context of Iran's health system by involving three main stakeholders. Previous studies have reported that people make informal payments to express gratitude (3,24,25), to get additional or better services (3,26), or because of cultural norms ingrained in their tradition, and weak laws (25). This study indicates that all of the above mentioned factors affect patients' decisions to make such payments, although some of them seem to play a more important role.…”
Section: Discussionmentioning
confidence: 62%
“…These payments can jeopardize governments' attempts to improve equity and access to care and policies targeted to the poor [3]. Informal payments are conceptualized as strategies to cope with lack of resources and poor performance at both the demand and supply side [4]. In some cases patients pay informally to jump the queue, receive better quality of services or more care [4], hence such payments have the potential of limiting access to healthcare services to patients who have more ability to pay rather than those most in need [5].…”
Section: Introductionmentioning
confidence: 99%
“…Informal payments are conceptualized as strategies to cope with lack of resources and poor performance at both the demand and supply side [4]. In some cases patients pay informally to jump the queue, receive better quality of services or more care [4], hence such payments have the potential of limiting access to healthcare services to patients who have more ability to pay rather than those most in need [5]. This is especially pertinent in the control of endemic diseases such as malaria, where informal payments can limit the financial access of the people to malaria treatment services.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the middle-income countries of Eastern Europe and the western republics of the former Soviet Union show that private OPEs have functioned as the primary means of filling the gap in funding for healthcare, which emerged as a result of the continuing economic constrains in public financing (Aarva et al 2009;Cockcroft et al 2008;Szende and Culyer 2006;Lohlein et al 2003). The situation is even more dire in the transitional countries of the Caucasus and Central Asia, where money coming from OPEs have become the major source of healthcare financing, and where OPEs far exceed public levels of funding (Balabanova et al 2004;Bonilla-Chacin et al 2005;Gotsadze et al 2005;Belli et al 2004;Sari et al 2000;McKee et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in middle-income countries emphasize the importance of OPE payments to personnel (Aarva et al 2009;Cockcroft et al 2008;. In contrast, scattered evidence from low-income transitional countries highlights a major role of OPE payments for supplies and medication (Habibov 2010;Ensor and Savelyeva 1998).…”
Section: Introductionmentioning
confidence: 99%